Comparative genomic analysis provides insight into the phylogeny and virulence of atypical enteropathogenic escherichia coli strains from Brazil - Hernandes, Rodrigo T. [UNESP]; Hazen, Tracy H.; Dos Santos, Luís F.; Richter, Taylor K. S.; Michalski, Jane M.; Rasko, David A. (Public Library of Science (PLoS), 2020)
Background Atypical enteropathogenic Escherichia coli (aEPEC) are one of the most frequent intestinal E. coli pathotypes isolated from diarrheal patients in Brazil. Isolates of aEPEC contain the locus of enterocyte effacement, but lack the genes of the bundle-forming pilus of typical EPEC, and the Shiga toxin of enterohemorrhagic E. coli (EHEC). The objective of this study was to evaluate the phylogeny and the gene content of Brazilian aEPEC genomes compared to a global aEPEC collection. Methodology Single nucleotide polymorphism (SNP)-based phylogenomic analysis was used to compare 106 sequenced Brazilian aEPEC with 221 aEPEC obtained from other geographic origins. Additionally, Large-Scale BLAST Score Ratio was used to determine the shared versus unique gene content of the aEPEC studied. Principal Findings Phylogenomic analysis demonstrated the 106 Brazilian aEPEC were present in phylogroups B1 (47.2%, 50/106), B2 (23.6%, 25/106), A (22.6%, 24/106), and E (6.6%, 7/106). Identification of EPEC and EHEC phylogenomic lineages demonstrated that 42.5% (45/106) of the Brazilian aEPEC were in four of the previously defined lineages: EPEC10 (17.9%, 19/106), EPEC9 (10.4%, 11/106), EHEC2 (7.5%, 8/106) and EPEC7 (6.6%, 7/106). Interestingly, an additional 28.3% (30/106) of the Brazilian aEPEC were identified in five novel lineages: EPEC11 (14.2%, 15/106), EPEC12 (4.7%, 5/106), EPEC13 (1.9%, 2/106), EPEC14 (5.7%, 6/106) and EPEC15 (1.9%, 2/106). We identified 246 genes that were more frequent among the aEPEC isolates from Brazil compared to the global aEPEC collection, including espG2,espT and espC (P<0.001). Moreover, the nleF gene was more frequently identified among Brazilian aEPEC isolates obtained from diarrheagenic patients when compared to healthy subjects (69.7% vs 41.2%, P<0.05).Conclusion The current study demonstrates significant genomic diversity among aEPEC from Brazil, with the identification of Brazilian aEPEC isolates to five novel EPEC lineages. The greater prevalence of some virulence genes among Brazilian aEPEC genomes could be important to the specific virulence strategies used by aEPEC in Brazil to cause diarrheal disease.